NATURAL APPROACH - Tinambunan, Erbin -; Ginting, Siti Aisah (Universitas Negeri Medan, 2014)
ABSTRACT This study deals with improving stuudents™ achievement in reading comprehension through natural approach. The objective of this study is to iinvestigate whether there is any significant improvement of the students™ achievement in reading comprehension when it is taught by using natural approach. The subject of the study was Grade XI students of Nasrani 3 Private Senior High School (Sekolah Menengah Atas Swasta Nasrani 3) Medan. There were thirty one students. They were taught by using Natural Approach. The instrument for data collection were teacher made test, observation sheet and questionaire. The techniques of data analysis applied were quantitative and qualitative. In analysing the data, the students were given three reading tests namely, Orientation Test, Test Cycle I and Test Cycle II. The mean of the students™ score for the first reading test as Orientation test was 51.61 the second reading test as Cycle I test was 66.61 and the third reading test as Cycle II test was 76.61. The total percentage of the improvement from the first reading test to the third was 77.41%. the conclusion is that the procedures of natural approach can improve the students™ achievement in reading comprehension. The qualitative data shows that the students were enthusiastic and interested in reading comprehension. It is suggested that teachers should apply Natural Approach as one of the media in improving students™ achievement in reading comprehension. Keywords: Reading, Natural Approach, classroom Action Research.